RETHINKING THE RELATIONSHIP CONSUMPTION, BODY AND APPEARANCE - Petenussi, Felipe Roberto [UNESP] (Univ Nac Cordoba, Centro Estudios Avanzados, 2016)
The present paper aims to demonstrate the narrow relation between the consumer culture and the media - understood as mediators of socio-cultural relations-in the current days, as the media puts into action signification formation processes through different practices, consumer goods and habits of consumption. These processes generate games of appearance that allow negotiation in the construction of the individual image through the use and consumption related to clothing, fashion and also the body. Moreover, the anthropological approach to consumption itself and the appearance are problematized by showing that these relations are symbolic constructions in which the terms used must be understood from the context of its production.
Keywords: consumption; body; appearance; identity; Media